Love in the coordines of desire and pleasure: philosophical-cultural sight - V.E. Turenko, (Ukrainian Cultural Studies, 2018)
In the article, on the basis of theoretical developments of contemporary foreign philosophers, illumination of love discourse in the coordinates of desire and pleasure is carried out. The author proves that love desire has not only a purely physical boundary; it includes not just sexual, but also purely spiritual and soul aspects (caring, support, forgiveness, etc.). The author substantiates the opinion that pleasure in love is also multifaceted; it does not concern only the physiological, instinctive needs of human nature. Based on the opinions of Western researchers, one can talk about the great significance of the phenomenon of pleasure in the discourse of love, because it is also connected with such aspects as overcoming the shortcoming, liberation from pressure, personally significant self-realization and self-affirmation. The author analyzes theoretical works by foreign researchers R. Apresyan, R. Barthes, J. Baudrillard, G. Bataille, P. Yevdokimova, G.-G. Gadamer, H. Yannaras, on the basis of which comes to the conclusion that satisfaction with the experience of personally meaningful self-realization and self-affirmation is an inevitable sign of love. The author investigates such aspects of love as "miraculous" (in the context of the application to Plato's “Symposium”), as well as "childhood" within the ideas of S. Freud and J. Baudrillard. Thus, the purpose of the article is to carry out a comprehensive analysis of the phenomenon of love, through the riot of historical-philosophical and cultural studies.
Keywords: desire, pleasure, love, discourse of love, train, object of love